การนำ BIM มาประยุกต์ใช้ในช่วงก่อนงานก่อสร้างอาคารชุดพักอาศัยภาคเอกชนในประเทศไทย ระหว่างปี พ.ศ. 2559-2564 - ธีระพงษ์ อินทรพาณิชย์ (จุฬาลงกรณ์มหาวิทยาลัย, 2023)
The adoption of BIM in the construction industry of private sector in Thailand has become widespread, offering both advantages and limitations during the construction process. The project development phase can be categorized into three main stages: Design phase, Construction phase, and Facility Management phase, each with specific data requirements. However, the data transmission between the Design phase and the Construction phase, known as Pre-construction, still lacks clarity. Pre-construction work is a crucial step that significantly influences project success. The objectives of this research were process, situations, factors, and recommendations for the BIM Adoption in Pre-construction. This research aims to study the model and process of BIM implementation during the Pre-construction period. This research adopts a study methodology that involves data collection through interviews with stakeholders in the Pre-construction phase of private sector residential condominiums in Thailand. Additionally, data from BIM Standards and BIM Guide is studied to be analyzed to find consistency, situations, factors, problems, obstacles, and recommendations for the appropriate of BIM. The results from research found that the BIM implementation model used in the case study was the Design-Bid-Build model. This model requires data transfer between various organizations, potentially leading to data discrepancies. However, the adoption of BIM can address such issues, as it operates as a connected information system throughout the project. BIM offers advantages in data transmission, quantity take-off, cost estimation, and early identification of construction issues. These factors have been found to improve efficiency and reduce errors in work. Problems and obstacles were found to be the increased work time during the pre-construction period and it was suggested that Personnel with skills in working with BIM should be increased, and government support should be obtained.